Поширення та характеристика рідкісних біотопів м. Києва - Альошкіна, У.М. (Український ботанічний журнал, 2011)
Представлены фитоценотические характеристики и карты распространения редкостных биотопов в г. Киеве в соответствии с европейскими природоохранными директивами: Бернской конвенцией (Council of Europe Bern Convention Res., No. 4, 1996), Директивами по охране местообитаний (EU Habitats Directive Annex I) и «Зеленой книгой Украины» (2009). The phytosociological aspects of rare habitats in Kyiv and scheme maps of their distribution are given in the article. Rare habitats were chosen following the Council of Europe Bern Convention Res. No. 4 1996 and the EU Habitats Directive Annex I, and according to the Green Data Book of Ukraine (2009).